EFL STUDENTS’ PERCEPTION ON TEACHERS’ ROLES IN ONLINE LEARNING ENVIRONMENT: A STUDY SURVEY - Fhazil Adzikri; Anandayu Suri Ardini (Jurnal Bahasa Lingua Scientia, 2022)
As a result of the COVID-19 epidemic, public schools have been obliged to switch from face-to-face instruction to online or distance learning only. Teachers may have a more challenging time dealing with the pandemic since they are used to working offline and now must do so online. This study aims to determine how EFL students perceive instructor responsibilities in an online learning environment, and the study's difficulty is how these students perceive teacher roles. The Scale of Teacher Role Inventory (STRI), a tool established by Huang, is utilized to gather data for this study. Student feedback on their work, emotional support, and classroom management were all useful in the results from the three sections. To complete this study question's data, English language education students from a Yogyakarta university were requested to answer 27 questions. Each portion of the questionnaire had varied findings, although the values were comparable. In the cognitive role component, students appreciated lecturers' comments or feedback on their work (M=4.58 SD=0.64), but practice question advice earned the lowest score (M=4.34 SD=0.73). In terms of emotion, the lecturer has offered good help, with the best score received when the lecturer encouraged students to explore their answers and results (M = 4.32, SD = 0.72) and the lowest score gained when the lecturer made learning stressful (M = 3.29, SD = 1.32). This component is the lowest, but the computation is reversed, showing that students are not under pressure from lecturers. Students believed the lecturer crafted a good semester-long course plan (M=4.52, SD=0.61). Students considered lecturers lacked control over learning rate hence this assessment utilized the lowest possible score (M = 4.15, SD = 0.85).